PENDIDIKAN NABI IBRAHIM DAN ANAKNYA DALAM PERSPEKTIF AL-QUR‘AN (Q.S. al-Shafat [37]: 102 - 107) - Budihardjo Budihardjo (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
This article elaborates the practice of education carried out by the prophet Ibrahim in the qur’anic perspectives, mainly stated on the Qur’an Surah ash-Shaffat [37]: 101-107. By exploring the grammatical meaning of verses, socio-historical background (asbabun nuzul), and the relation among verses (munasabah), several aspects of the education of the prophet Ibrahim a.s. are highlighted. Those are spirituality based education, dialogue, patience, and fidelity during the educational process.